Characterization of non-solvent precipitated starch using asymmetrical flow field-flow fractionation coupled with multiple detectors. (15th February 2019) - Fuentes, Catalina; Saari, Hisfazilah; Choi, Jaeyeong; Lee, Seungho; Sjöö, Malin; Wahlgren, Marie; Nilsson, Lars
Highlights: Non-solvent precipitated starch (non-SPS) is obtained from waxy maize starch. Precipitated starch properties after re-dispersion depend on the preparation method. Precipitated starch has an amorphous structure. Re-dispersion at room temperature can lead to dissolution of starch precipitates. Size, molar mass, apparent density, and conformational properties are determined. Abstract: Non-solvent precipitated starch (non-SPS) is a novel component for starch-based emulsions. Herein, three non-SPS materials were prepared using ethanol as a precipitant of waxy maize starch granules (WMs). The WMs were either untreated (SP) or pre-treated via acid-hydrolysis (AHSP). In addition, SP was modified using n-octenyl succinic anhydride (OSA), yielding OSASP. This study aimed to investigate the influence of the non-SPS preparation method on the size, molar mass (M), and apparent density (ρapp ) of the materials when subjected to different dissolution/dispersion procedures using asymmetrical flow field-flow fractionation (AF4). The results showed that the molar mass, size, and apparent density depended on the type of non-SPS with a decrease in Mw (1.8–9.4 g/mol) and rrms (60–148 nm) upon re-dispersion in different media in the order: SP > OSASP > AHSP. Moreover, different types of non-SPS materials displayed different conformational properties and were stable in aqueous solution at room temperature in the investigated time (24 h).